The health of the children - residents of radiation-contaminated territories, born after the Chornobyl disaster (Environment & Health, 2019)
Objective: We studied the structure of non-neoplastic diseases of the descendants of the first generation, the residents of the of radiation-contaminated territories, born in 1987 - 1999.Materials and methods: The database of the State Register of Ukraine (SRU) of the suffered from the ionizing radiation as a result of the accident at the Chornobyl NPP was a source of information. The base cohort made up 15 174 descendants (7 681 males, 7 493 females). Depending on the date of birth after the accident, four groups with the age interval of 0–3 years were formed: the first group was from 03.03.1987 to 28.02.1990, the second group - from 01.03.1990 to 02.28.1993, the third group - from 01.03.1993 to 28.02.1996, the fourth one – from 03.01.1996 to 02.28.1999. The period of epidemiological study constituted 18 years from the date of birth of the descendants. We studied the structure of non-neoplastic diseases. The parameter was calculated with the help of the Microsoft Office Excel 2013 software package.Results: First, as a result of the epidemiological study, the features of changes in the structure of non-neoplastic diseases in the descendants of the first generation, depending on the date of birth after the accident, are shown. The diseases of the respiratory, digestive, and endocrine systems played the main role in the change of the structure and accounted for the majority of all diseases (75%). At the same time, diseases of the respiratory organs prevail in the boys, endocrine pathology and diseases of digestive organs prevail in the girls.The dependence of the development of non-neoplastic diseases on the time of the accident at the Chornobyl NPP and the date of birth of the descendants was revealed. The proportion of respiratory diseases, mental and behaviour disorders, as well as congenital anomalies and malformations doubled in the children born in 10-12 years after the accident in comparison with the children born in the first years after the accident.At the same time, there is a decrease in the proportion of the diseases of the endocrine and digestive systems, depending on the years of birth of the children after the Chornobyl disaster.Conclusions: The dependence of the development of non-neoplastic diseases by the studied classes of diseases on the time of birth after the accident at the Chornobyl NPP was revealed in the descendants of the first generation of the residents of radiation-contaminated areas.The results of the epidemiological analysis are preliminary and require the further deep research.
Keywords: the descendants of the first generation; radiation-contaminated territory; non-neoplastic diseases; date of birth after the Chornobyl disaster